Environment, Economy and Society – the Body, Mind and Soul of Sustainable Design of Buildings - Venkatesh, G (Problemy Ekorozwoju, 2023)
The design process in general, and the one for buildings in particular has evolved and become increasingly intricate, with additional layers and factors becoming relevant, as the drive towards sustainability (the Sustainable development goals defined by the United Nations in 2015) has gathered steam. This short chapter focuses on the diversity of issues which sustainable building design is likely to be influenced by, in the years ahead.